FUN SCIENCE AND ISLAMIC EDUCATION FOR KIDS DI TPA KHADIJAH - Muhammad Afif Rizki Sudirman; Dwi Yuni Damayanti; Fatimah Az-zahra Abdillah; Mahdalena; M. Fawwaz Ferriansyah; Najwa Dzakirah Nailah; Nurazizah Salshabila; Septi Jualiah Wardani; Nunung Nurhasanah (UIN Sunan Kalijaga, 2022)
Nowadays the Koran is often seen as a sacred book that only regulates religious matters, neglecting messages from other aspects including scientific issues (science). Our group in the KKN program offered an activity carried out under the name Fun Science and Education for Kids to introduce the relationship between the Qur'an and natural phenomena around us. After making observations at the Khadijah TPA, 3 science experiments were designed for the TPA children, namely the process of rainbow occurrence, volcanic eruptions, and rain. The three experiments are linked to 3 verses in the Koran. The evaluation was carried out on the acceptance of science material and its link with the Koran by the participants. Of the 6 questions, the TPA children managed to give 5 correct answers. Khadijah TPA participants seemed to interact with enthusiasm and good comprehension.